Mannosylated thiolated polyethylenimine nanoparticles for the enhanced efficacy of antimonial drug against Leishmaniasis. (January 2018) - Sarwar, Hafiz S; Ashraf, Sehreen; Akhtar, Sohail; Sohail, Muhammad F; Hussain, Syed Z; Rafay, Muhammad; Yasinzai, Masoom; Hussain, Irshad; Shahnaz, Gul
Aim: Our aim was to inhibit trypanothione reductase (TR) and P-gp efflux pump of Leishmania by the use of thiolated polymers. Thus, increasing the intracellular accumulation and therapeutic effectiveness of antimonial compounds.Methods: Mannosylated thiolated chitosan and mannosylated thiolated chitosan-polyethyleneimine graft were synthesized and characterized. Meglumine antimoniate-loaded nanoparticles were prepared and evaluated for TR and P-gp efflux pump inhibition, biocompatibility, macrophage uptake and antileishmanial potential.Results: Thiomers inhibited TR with Ki 2.021. The macrophage uptake was 33.7- and 18.9-fold higher with mannosylated thiolated chitosan-polyethyleneimine graft and mannosylated thiolated chitosan nanoparticles, respectively, as compared with the glucantime. Moreover, the in vitro antileishmanial activity showed 14.41- and 7.4-fold improved IC50 for M-T CS-g-PEI and M-TCS, respectively as compared with glucantime.Conclusion: These results encouraged the concept that TR and P-gp inhibition by the use of thiomers improves the therapeutic efficacy of antimonial drugs.